Post-marketing surveillance of upadacitinib: multilevel analysis of venous thromboembolism reporting in global data and rheumatoid arthritis - Ferreira-da-Silva, Renato; Lobo, Mariana; Abreu, Ana Rafaela; Pereira-Macedo, Juliana; Mós, Beatriz; Rodriguez, Carolina Ameijeiras; Lourenço, Inês Mariana; Vieira, Isabel; Polónia, Jorge Junqueira; Gouveia, Luís; Silva, Lurdes; Morato, Manuela; et al. (Frontiers in Medicine, 2025)
BackgroundUpadacitinib is an oral Janus kinase 1 (JAK1) selective inhibitor approved for the treatment of rheumatoid arthritis (RA) and other immune-mediated inflammatory diseases. Concerns have emerged regarding a potential increased risk of venous thromboembolism (VTE) with JAK inhibitors (JAKi), though real-world evidence remains limited.ObjectiveTo assess the post-marketing safety profile of upadacitinib in relation to VTE using global pharmacovigilance data.MethodsWe conducted a disproportionality analysis using Individual Case Safety Reports (ICSRs) from VigiBase, accessed via VigiLyze, including all reports up to February 20, 2025. Upadacitinib was compared with: (i) all other medicines; (ii) other second-line advanced RA therapies (bDMARDs and tsDMARDs); and (iii) other JAKi (baricitinib, tofacitinib, filgotinib). Reporting Odds Ratios (ROR) and Information Components (IC), with 95% confidence intervals, were calculated.ResultsDescriptive analyses identified 678 VTE cases with upadacitinib, predominantly affecting women (68.1%), with a median age of 63 years. Most were classified as serious (91.2%), although fatal outcomes were less frequent than with comparators. In disproportionality analyses, upadacitinib showed a significant signal versus all medicines (ROR: 2.08; IC: 1.04) and versus other second-line therapies (ROR: 1.40; IC: 0.41), but not versus other JAKi (ROR: 0.98; IC: –0.04). In 2023, disproportionality declined, particularly relative to other JAKi (ROR: 0.57; IC: –0.38).ConclusionUpadacitinib-related VTE cases display distinct clinical characteristics. These findings support continued pharmacovigilance and the need for robust real-world studies to clarify absolute and comparative risks, inform regulation, and guide personalised therapeutic strategies in RA.